DATA PROCESSING SYSTEM OR SERVICE EMPLOYEE POPULATION JAKARTA PROVINCE EMPLOYMENT IN THIS SUB PART USING MICROSOFT ACCESS - Gentina Arifin; Aqwam Rosadi Kardian, Skom.,MM. (Jurnal Sistem Informasi, 2001)
There are still many government agencies that the staffing data processing using the manual way, so it requires a computerized data processing system to assist the staffing data processing. Official residence of DKI Jakarta Province, in the implementation of government need to use a processing system, computer-based database.